Assessing the impact of an online inquiry teaching intervention on sixth graders' search performance - Roberto González-Ibáñez; Daniel Gacitúa; Gonzalo Martínez-Ramírez; Jacqueline Köhler; Eero Sormunen; Carita Kiili; Mirjamaija Mikkilä-Erdmann; Norbert Erdmann; Marja Vauras; Paavo H.T. Leppänen (Germany, 2022)
The study of online inquiry competences (OIC) is an important topic on the information literacy (IL) field. Most of the work has been focused on higher education and high-school students, while less has been done regarding primary education. In this work we investigate the effects of an OIC teaching intervention on search performance of a large group of sixth graders from Finland. Our preliminary results show significant improvements in search performance on the intervened group of students compared to a control group when working on a science research task. This work shed light about the potential benefits of a particular approach to develop OIC on elementary school students.
Proceedings of the CIKM 2020 Workshops